1970
DOI: 10.4315/0022-2747-33.11.484
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Viruses in Low Moisture Foods

Abstract: Reovirus type 1, influenza virus type A, and parainfluenza virus type 3 persisted for ≤ 3 days in the low-moisture foods tested. Then enteroviruses tested persisted > 2 weeks at room temperature and > 2 months in the refrigerator. Where storage temperature was not constant, time-temperature effects were roughly cumulative. Inactivation of enteroviruses proceeded at an intermediate rate in foods stored at an intermediate temperature of 12 C. Polioviruses from feces and from tissue cultures were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…His data are very difficult to summarize, but the results were generally as stated above. Similar findings were reported for poliovirus type 1 in several foods of normal moisture content by Heidelbaugh and Giron 102 and for three enteroviruses in low moisture foods by Cliver et al 103 Comparable data are not generally available for other viruses as secondary contaminants in foods.…”
Section: Modifying Factorssupporting
confidence: 82%
See 4 more Smart Citations
“…His data are very difficult to summarize, but the results were generally as stated above. Similar findings were reported for poliovirus type 1 in several foods of normal moisture content by Heidelbaugh and Giron 102 and for three enteroviruses in low moisture foods by Cliver et al 103 Comparable data are not generally available for other viruses as secondary contaminants in foods.…”
Section: Modifying Factorssupporting
confidence: 82%
“…This was evident at 5°C with poliovirus in a "bland" food adjusted to pH 5.5 with propionic acid, and the effect was more pronounced at pH 4. 103 Similar results can generally be expected with enteroviruses in naturally acid foods, although the picture is complicated in the presence of significant levels of salts and proteins. We found that these last components have little effect upon enterovirus stability at 5°C in food near pH 7 but that they may (at the tested levels) enhance virus inactivation individually at pH 5.5, yet combine to stabilize the virus.…”
Section: Modifying Factorssupporting
confidence: 70%
See 3 more Smart Citations